Assessment Of Mechanical And Durability Properties Of Concrete Containing GGBFS And Silica Fume Under HCL Exposure (Journal of Pharmaceutical Negative Results, 2022)
In recent decades, global warming and CO2 emissions have made sustainable development a priority. Diverse industrial sectors are rapidly developing innovative technology while coping with waste disposal concerns. Waste management issues in numerous areascontribute to pollution in the environment. Concrete can be manufactured by substituting various industrial wastes for cement, and attempts are undertaken to reduce environmental emissions and waste management principles. Industrial waste is now being used in concrete to provide the best choice for the environment and the construction industry to generate sustainable concrete. In the current investigation, various percentages of industrial waste, such as ground granulated blast furnace slag (GGBFS) up to 50% and Silica Fume up to 20%, were employed for concrete preparation. The compressive strength of hardened concrete was evaluated after a 28-day curing period. After that, concrete was exposed to HCL for 90 days and 180 days to assess deterioration in an aggressive environment. Concrete was also subjected to some non-destructive testing (NDT) to assess strength degradation. Microstructure and regression analysis were also performed. The results of this study were positive, demonstrating that concrete with optimal waste replacement enhances physical qualities.